一种加重聚磺修井液高温高压静态沉降稳定性预测方法 (2024)
本发明公开了一种加重聚磺修井液高温高压静态沉降稳定性预测方法，包括：基于沉降稳定性试验装置得到沉降因子的测量值；获取简化后的沉降参数量纲和基本量纲；采用矩阵运算构造得到沉降参数的无量纲数；对无量纲数进行多元非线性回归处理，得到修井液沉降稳定性关联模型；根据修井液沉降稳定性关联模型得到沉降因子的预测值；将沉降因子的测量值与沉降因子的预测值进行对比，以验证修井液沉降稳定性关联模型的可靠性。本发明能有效预测固相加重聚磺酸盐修井液的静沉降稳定性，可以指导固相加重聚磺酸修井液的参数调整，以达到所需的沉降稳定性，为固相加重修井液沉降稳定性的预测和控制提供了一种新的方法。 The invention discloses a method for predicting high-temperature and high-pressure static sedimentation stability of weighted polysulfonate workover fluid. The method comprises the following steps: obtaining a measured value of a sedimentation factor based on a sedimentation stability test device; obtaining simplified settlement parameter dimensions and basic dimensions; constructing by adopting matrix operation to obtain a dimensionless number of the settlement parameter; performing multivariate nonlinear regression processing on the dimensionless number to obtain a workover fluid settlement stability correlation model; obtaining a predicted value of a settlement factor according to the workover fluid settlement stability correlat